2005
DOI: 10.1101/gad.339405
|View full text |Cite
|
Sign up to set email alerts
|

The growing pre-mRNA recruits actin and chromatin-modifying factors to transcriptionally active genes

Abstract: In the dipteran Chironomus tentans, actin binds to hrp65, a nuclear protein associated with mRNP complexes. Disruption of the actin-hrp65 interaction in vivo by the competing peptide 65-2CTS reduces transcription drastically, which suggests that the actin-hrp65 interaction is required for transcription. We show that the inhibitory effect of the 65-2CTS peptide on transcription is counteracted by trichostatin A, a drug that inhibits histone deacetylation. We also show that actin and hrp65 are associated in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 63 publications
6
55
0
Order By: Relevance
“…These observations are in agreement with the results of our previous investigation in which we found the colocalization of SATB1 and F-actin in the transcriptionally active regions of the nuclei of CHO AA8 cells undergoing active cell death [24]. Many authors showed that actin may translocate into the cell nucleus to function as a transcriptional modulator of gene expression [1,3,[32][33][34][35][36]. We have previously demonstrated not only the translocation of F-actin into the nucleus, but also its involvement in chromatin remodeling during cell death [19][20][21][22][23].…”
supporting
confidence: 82%
“…These observations are in agreement with the results of our previous investigation in which we found the colocalization of SATB1 and F-actin in the transcriptionally active regions of the nuclei of CHO AA8 cells undergoing active cell death [24]. Many authors showed that actin may translocate into the cell nucleus to function as a transcriptional modulator of gene expression [1,3,[32][33][34][35][36]. We have previously demonstrated not only the translocation of F-actin into the nucleus, but also its involvement in chromatin remodeling during cell death [19][20][21][22][23].…”
supporting
confidence: 82%
“…The presence of actin within the nucleus was first suggested in 1969 (20), but its role in the nucleus has been extremely controversial. One of the first demonstrations of a role for actin in the nucleus was as a collaborating factor in chromatin remodelling (21), an idea that has been increasingly confirmed and extended (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme consists of 12 subunits named Rpb1 to Rpb12 in humans (Hampsey 1998). Evidence has shown that actin is a component of the Pol II PICs and acts as a platform for the recruitment of histone acetyltransferase (HAT) or histone deacetylase (HDAC) to the active transcription unit (Kukalev et al 2005;Sjolinder et al 2005;Obrdlik et al 2008). Moreover, actin could be affinity-purified with an Rpb4/Rpb7 column (Mitsuzawa et al 2005), raising the possibility that actin could interact with Pol II directly.…”
Section: Introductionmentioning
confidence: 99%